The Role Of Social Status As Seen In Aladdin Movie - susilawati, susilawati (English Language, Linguistics, Literature, And Education Journal, 2021)
The main objectives of this research are (1) to find out what kinds of Social Status as seen in Aladdin Movie (2019). (2) to describe how the role of Social Status as seen Aladdin Movie (2019). The researcher uses Mayor Polak (1979) and Wuradji (2009) Theory. This research uses descriptive qualitative method. The finding of this research shows that the Social Status as seen in Aladdin movie: (1) there are three types of Social Status as seen Aladdin movie, they are Ascribed Status, Achieved Status and Assigned Status. Ascribed status was mostly dominant used in this movie because the background of this movie is based on a kingdom in which a monarchical government system, led by a king and throne of the kingdom will be inherited to his lineage. (2). The role of a leader is different from that of ordinary people because social status they have, the leader has an obligation to ensure the welfare and safety of the community, the leader also protects each member so that they are in accordance with the goals achieved. Different things with ordinary people they are obliged to follow the rules and respect a leader.